GATA-3 deficiency abrogates the development and maintenance of T helper type 2 cells - Pai, Sung-Yun (National Academy of Sciences, 2004)
T helper type 2 (Th2) cells secrete IL-4, IL-5, IL-10, and IL-13 and mediate allergic and asthmatic disease. GATA-3 is a Th2-specific transcription factor that appears in overexpression studies and transgenic systems to function as a Th2 lineage determinant. Because GATA-3 is also crucial for development of the T lineage and throughout thymic development, direct demonstration that GATA-3 is required for Th2 development by targeted deletion has been lacking. Using a conditional knockout approach, we found that GATA-3 is required for optimal Th2 cytokine production in vitro and in vivo. Our data also show that GATA-3 expression must be sustained to maintain the Th2 phenotype.